Sistem Monitoring Kebakaran Dini Berbasis ESP8266 Menggunakan Sensor Api dan Firebase Realtime Database - Muhamad Bahrul A’lam; Sujono Sujono (JOURNAL SAINS STUDENT RESEARCH, 2026)
Fire is a frequent disaster and can cause significant losses, both in terms of material and human safety. Delays in detecting fires are a major factor in their impact. Therefore, an early fire monitoring system capable of providing information quickly and in real time is needed. This research aims to design and implement an Internet of Things (IoT)-based early fire monitoring system using the ESP8266 module as the main controller, a fire sensor as a flame detector, and the Firebase Realtime Database as a medium for online data storage and monitoring. This system works by detecting the presence of fire through the fire sensor, then the ESP8266 sends the detected data to Firebase in real time. This information can be monitored through an application or web monitoring. Test results show that the system is able to detect fire effectively and transmit data to Firebase quickly and stably, making it suitable for use as an early fire warning system.